Performance of the DFT-D method, paired with the PCM implicit solvation model, for the computation of interaction energies of solvated complexes of biological interest - Riley, Kevin E; Vondrášek, Jiří; Hobza, Pavel (PCCP. Physical chemistry chemical physics, 2007)
In this work we investigate the performance of the DFT method, augmented with an empirical dispersion function (DFT-D), paired with the PCM implicit solvation model, for the computation of noncovalent interaction energies of biologically-relevant, solvated model complexes. It is found that this method describes intermolecular interactions within water and ether (protein-like) environments with roughly the same accuracy as in the gas phase. Another important finding is that, when environmental effects are taken into account, the empirical dispersion term associated with the DFT-D method need be modified very little (or not at all), in order to obtain the optimum, most well balanced, performance.
Keywords: vodíková vazba; roztoky; povrchové vlastnosti; Macromolecular Substances; přenos energie; proteiny; RNA; Algorithms; Solutions; Hydrophobic and Hydrophilic Interactions; chemické modely; Proteins; termodynamika; Models, Biological; rozpustnost; makromolekulární látky; Energy Transfer; DNA; Quantum Theory; Thermodynamics; Models, Chemical; kvantová teorie; biologické modely; Solubility; algoritmy; Hydrogen Bonding; Surface Properties; hydrofobní a hydrofilní interakce